Self-Stigma in Parkinson's Disease: A 3-Year Prospective Cohort Study - Lin, Junyu; Ou, Ruwei; Wei, Qianqian; Cao, Bei; Li, Chunyu; Hou, Yanbing; Zhang, Lingyu; Liu, Kuncheng; Shang, Huifang (Frontiers in Aging Neuroscience, 2022)
Purpose: Self-stigma is common in patients with Parkinson's disease (PD) and may lead to social isolation and delayed search for medical help. We conducted a three-year prospective longitudinal study to investigate the development and evolution of self-stigma in patients with early-stage PD and to explore the associated and predictive factors of self-stigma in PD. Method: A total of 224 patients with early-stage PD (disease duration < three years) were enrolled at baseline and followed up annually for three consecutive years. Self-stigma was assessed by the stigma subscale of the Parkinson's Disease Questionnaire (item 23-26). The generalized estimating equations model was applied to investigate the associated factors of self-stigma over three years, and the binary logistic model was used to explore the predictors of self-stigma in PD patients without self-stigma at baseline. Results: The prevalence of self-stigma decreased from 58.0% at baseline to 49.2% after three years. The Hamilton Depression Rating Scale (HDRS) score was the only associated factor (B 0.160 [1.106-0.214], P < 0.001) of self-stigma over three years and the only predictor (OR 1.252 [1.044-1.502], P = 0.015) of the onset of self-stigma. Conclusion: Self-stigma is very common in PD, but its prevalence tends to decrease as the disease progresses. Depression was the only associated and predictive factor of self-stigma in PD and could be an effective target of alleviating self-stigma.